APPLICATION ENERGY SAVING IN DHARMAWANGSA HOTEL WITH A SUSTAINABLE ARCHITECTURAL APPROACH - Terra, Alfarizy; Steven, Gabriel; Elviana, Eva (ADBE, 2023)
The hospitality industry in Indonesia, especially in Jakarta, is progressing rapidly thanks to its strategic position as the center of government. This growth is supported by the presence of facilities around the hospitality area. However, the increase in facilities also implies large energy usage, especially by hotels that operate all year round. Inefficient energy use will be an important issue in the future, especially in a country with a large population like Indonesia. This research aims to identify the design strategies used by Dharmawangsa Hotel in Jakarta in saving energy use in its building. The research method used is a descriptive qualitative method with secondary data analysis based on the principles of sustainable architecture. The results showed that Dharmawangsa Hotel has successfully implemented several strategies to save energy. The use of large openings in the building allows maximum natural lighting in the room, thus reducing dependence on electric lights. In addition, the hotel also campaigns for efficient water usage to guests. These implementations have successfully reduced Dharmawangsa Hotel's electrical and water energy consumption.